Battery management in electric vehicles for smart grids - Pang, Gavin (2016)
With Singapore venturing into smart-grids in the latest few smart buildings [1]. V2G(Vehicle-to-Grid) would be incorporated to further reduce energy costs and increase energy efficiency. PEVs would be connected to the grid to reduce the peak demand and balance the energy consumption with supply. On the assumption that Singapore’s traffic usually is at its highest during ‘peak hours’, this study will show the amount variance with respect to PEVs available. Firstly, researches and data collection was executed to in preparation. Secondly, attention was on construction and testing of modules and components of Smart-Grid. Lastly, statistic analysis was done with heuristic data to achieve balance of energy and calculation of load variance.